Mediation Effect of Computer Self-Efficacy Between Learning Motivation and Learning Achievement (JEM17: Jurnal Ekonomi Manajemen, 2023)
Factors that influence learning achievement include learning motivation and self-efficacy. This study aims to explain the effect of learning motivation, and self-efficacy on student achievement. The population used in this study were students of the Faculty of Economics, University of 17 August 1945, Surabaya. The sampling technique is random sampling. The data collection used is documentation and questionnaires. The design of this research is an explanation of the variables of learning motivation (X1), self-efficacy (X2), and learning achievement (Y). The data analysis technique used is Linear Regression Analysis. The results showed that learning motivation and self-efficacy partially affected the learning achievement of undergraduate students. The limitations of this study are limited to students of the Management S1 program, so it cannot be generalized to other populations. Further researchers are expected to add other variables that affect learning achievement and can add data collection techniques with observation and interviews so that research results are more accurate. Keywords: Learning Motivation, Computer Self-Efficacy, Learning Achievement.